2018
DOI: 10.4103/jpi.jpi_69_17
|View full text |Cite
|
Sign up to set email alerts
|

Optimized JPEG 2000 Compression for Efficient Storage of Histopathological Whole-Slide Images

Abstract: Background:Whole slide images (WSIs, digitized histopathology glass slides) are large data files whose long-term storage remains a significant cost for pathology departments. Currently used WSI formats are based on lossy image compression alogrithms, either using JPEG or its more efficient successor JPEG 2000. While the advantages of the JPEG 2000 algorithm (JP2) are commonly recognized, its compression parameters have not been fully optimized for pathology WSIs.Methods:We defined an optimized parametrization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…21 With the use of the JPEG 2000 algorithm, it also becomes possible to store different parts of the same picture with different qualities, which makes it attractive for the compression of WSIs, 22 since ∼80% of a WSI area contains an empty (white) background region 23 that does not contain any tissue. Helin et al 24 showed that applying a very high degree of JPEG 2000 compression on the background part of WSIs and applying a conventional amount of compression (e.g., 35:1) on the tissue-containing part results in a high overall compression ratio. Compression gains of up to a factor 3 are reported compared to classical, nonadaptive compression with JPEG 2000.…”
Section: Introductionmentioning
confidence: 99%
“…21 With the use of the JPEG 2000 algorithm, it also becomes possible to store different parts of the same picture with different qualities, which makes it attractive for the compression of WSIs, 22 since ∼80% of a WSI area contains an empty (white) background region 23 that does not contain any tissue. Helin et al 24 showed that applying a very high degree of JPEG 2000 compression on the background part of WSIs and applying a conventional amount of compression (e.g., 35:1) on the tissue-containing part results in a high overall compression ratio. Compression gains of up to a factor 3 are reported compared to classical, nonadaptive compression with JPEG 2000.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, most WSI slide-scanner manufactures use 1 of these 2 approaches as the backbone of their proprietary formats. 19 , 30 , 31 As a result, their study is most likely to be relevant in the storage and transmission of WSI images. That said, as more powerful novel compression schemes are introduced, 32 tested, and routinely used in practice, future work will be required to evaluate their respective compression artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…JPEG and JPEG2000 20 lossy compression approaches were used in this study because they are most commonly used by scanner manufacturers and WSI formats. 19 JPEG allows the user to specify the desired level of compression via a quality score associated with the quantization of frequencies in the image. When employing JPEG2000, the user specifies a PSNR value, which results in the truncation of certain frequencies after a wavelet transformation.…”
Section: Methodsmentioning
confidence: 99%
“…However, the provided metrics will enable us to objectively compare further system configurations, additional viewers and scanners, to drive the development toward a seamless DP workflow. For example, further improvements of digital viewers that were not discussed in this study include pretiling of WSI, new image compression techniques 23,24 and advanced Web streaming. 25,26 With improved digital systems, we hypothesize, digital sign out will be on par or even more efficient than with a microscope.…”
Section: Influence Of Tile Size On Time Per Tile and Tfovmentioning
confidence: 99%